One-step, binder-free and rapid synthesis of high-entropy oxide anode materials for the lithium-ion batteries - Yuxin Lin; Shimiao Chen; Yangzhou Ma; Shuai Wang; Ziyang Ma; Lu Sun; Rui Cao; Guangsheng Song; Zexin Yu; Jianhua Yao; Hanlin Liao (Next Materials)
High-entropy oxides (HEOs) hold significant promise as next-generation lithium-ion battery anodes due to their entropy-driven structural stability and tunable electrochemical properties. However, scalable synthesis and composition optimization remain critical challenges. This study introduces a one-step solution precursor plasma spraying (SPPS) technique for rapid, binder-free fabrication of a six-component HEO (FeCoNiCuZnMgO1 −x), enabling large-scale production. Structural analyses (XRD, TEM) confirm a single-phase rock-salt structure with oxygen vacancies, which enhance Li+ diffusion kinetics and electronic conductivity. The HEO anode delivers a high initial discharge capacity (820.1 mAh g−1), retains 55.5 % capacity (455.2 mAh g−1) after 220 cycles, and exhibits robust rate capability (247.3 mAh g−1 at 2 A g−1). The synergistic ''cocktail effect'' from multi-metal redox activity and entropy-stabilized framework mitigates structural degradation, addressing cyclability challenges. Comparative analysis reveals superior performance to conventional transition metal oxide anodes, underscoring the efficacy of SPPS in tailoring HEOs. This work not only advances the mechanistic understanding of entropy-stabilized anodes but also provides a scalable pathway for industrial application, bridging the gap between laboratory innovation and commercial battery technology.